2012
DOI: 10.1071/ah11104
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation into beliefs about collaborative practice among maternity care providers

Abstract: Objective. To investigate agreement with the National Health and Medical Research Council (NHMRC) definition of collaboration in maternity care by care providers, and to examine their preferences for models of care in order to shed light on the lack of success in implementing collaborative practice.Methods. Maternity care providers completed a survey in Queensland. The final sample consisted of 337 participants, including 281 midwives (83.38%), 35 obstetricians (10.39%), and 21 general practitioners (6.23%).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In recent years, improvements have been made to integrate care providers in the shared-care model by implementing guidelines and specialised training utilising a patient centred focus. This focus requires incorporating direct links in health care provider communication and shared decision making, using consultation, referral, clinical prompts, education strategies, shared-care co-ordination and using a PHR [43,55,56,61-63]. Using the PHR in a GP shared-care model has been a successful initiative in integrating care and providing opportunities to link information between health care providers and women.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, improvements have been made to integrate care providers in the shared-care model by implementing guidelines and specialised training utilising a patient centred focus. This focus requires incorporating direct links in health care provider communication and shared decision making, using consultation, referral, clinical prompts, education strategies, shared-care co-ordination and using a PHR [43,55,56,61-63]. Using the PHR in a GP shared-care model has been a successful initiative in integrating care and providing opportunities to link information between health care providers and women.…”
Section: Discussionmentioning
confidence: 99%
“…This study formed part of a larger study on interprofessional collaboration reported elsewhere [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Advocating for the woman's choices or negotiating appropriate evidence based care is an essential midwifery capability that optimises outcomes for women and their babies (ANMC, 2006;Skinner and Foureur, 2010). Sound collaborative practice and engaging in critical conversations about care avoids tension caused by differing opinions which affect crucial clinical judgements (Watson et al, 2012;Van Helmond et al, 2015).…”
Section: • Negotiates Carementioning
confidence: 99%